Ameliorating proliferation and superoxide dismutase mRNA expression of cadmium exposed leukocytes through copper treatment in transitional dairy cows - KUMAR, M; KAUR, H; MANI, V; GUPTA, N; TYAGI, A K; KUSHWAHA, R (The Indian Journal of Animal Sciences, 2016)
The study was conducted to determine the effect of cadmium on lymphocyte proliferation and mRNA superoxide dismutase (SOD) expression and to evaluate whether copper treatment in Cd exposed lymphocytes can modulate their proliferation and SOD mRNA expression. Blood samples were collected from crossbred transitional dairy cows at –30, –15, 0, 15, and 30 days of calving and evaluated for lymphocytes proliferation and SOD expression. A fixed number of lymphocyte were cultured for 72 h with 10-3, 10-4, 10-5 and 10-6 M levels of Cd. Effect of different Cd levels on proliferation and mRNA SOD expression was counteracted by 30, 35 and 40 μM Cu. Mitogenic response of lymphocyte and mRNA expression of SOD reduced as the days of parturition advanced and was noted lowest at the day of calving. Lymphocyte proliferation and mRNA SOD expression showed negative correlation with Cd levels. Addition of Cu in the Cd exposed lymphocyte culture improved lymphocyte proliferation and relative abundance of SOD mRNA expression and increase was reported highest in 40 μM Cu treated lymphocytes. These results indicated that Cu can ameliorate adverse effect of Cd on lymphocyte proliferation and SOD expression in transitional dairy cows.